EFL Students' Entrepreneurial Tendencies: Is It a Misdirected Issue? - Isna Humaera; Ahmed Sardi; Fitri Amaliah Akbal; Ali Syahban Amir; Ruslan Hasyim; Nurdin Noni (EduLine: Journal of Education and Learning Innovation, 2023)
This paper examines the EFL students' tendencies toward entrepreneurship and whether this phenomenon is misdirected or not. It was investigated by using descriptive qualitative through thematic analysis. The findings showed that the EFL students had run some businesses and planned to run self-employed businesses shortly. This resulted in most students having run businesses that support their field of knowledge. These businesses are English language courses, translation or editing services, and private classes. This tendency made them have challenges in business competitiveness. Whether it was misdirected or not, that depended on the EFL students’ career opportunities. Thus, some of them tended to choose to open culinary businesses, online shops, and clothing stores that are more likely.